The role of good faith in real estate transactions with an official document - Hojjat Alizadeh Zinab (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Among the legal problems in the courts is the transaction of real estate with an official document. In such a way that the immovable property is transferred by a person other than the owner, with an official document, this transfer can be revoked and it does not matter whether this transfer was done in good faith and unknowingly or with malice and usurpation. And for example, if a few years ago, a property was transferred several times by a non-owner, with an official document, according to current regulations, it is possible to cancel the first transfer and all subsequent owners are considered usurpers and are the guarantor of the same interests to the owner. . To this end, in the present article, we intend to examine the current situation and the problems related to the official document, to examine the role of good faith in real estate transactions, and to see whether the person who owns it in good faith can have its property protected. As a result, it can be said that it is possible to protect the owner in good faith in real estate transactions with an official document, which also increases the validity and value of the official document.